Legal Challenges in Overcoming Changes in Social Behaviour Due to the Development of Technology and Information - Octaviani Suryanto, Salsa; Mulyana, Aji (Golden Ratio of Law and Social Policy Review, 2024)
The development of technology and information that is spread globally, especially in Indonesia, has a significant impact on changes in social behavior in people's lives. Technological developments not only affect behavioural changes but also affect the way of interacting, acting and communicating. Although it provides convenience for society and has a positive side that can help humans in all matters and fields, technology and information also pose serious legal challenges related to changes in social behaviour that occur in society, such as violations of privacy, freedom of speech and the spread of fake news. The research method used in this article is descriptive qualitative, literature study and reflection method. Data were collected through literature studies, articles, and legislation related to information technology. Therefore, this article aims to identify legal challenges that arise due to the development of information technology that causes changes in individual behaviour. So as to overcome these challenges, improvements and adjustments to laws relevant to the current technological era are needed such as the protection of privacy rights or personal data must be strengthened through strict regulations, law enforcement related to fake news needs to be improved and moral decline must also be addressed. The association between the government and legal bodies must work together to overcome the challenges that occur and maintain a balance between technological progress, legal protection and law enforcement. It is hoped that this article will provide a better understanding of the legal challenges faced due to the growing flow of technology, and provide awareness to each individual to understand in depth the negative impact of information technology.